MENINGKATKAN DAYA SAING PEREKONOMIAN NASIONAL: PELAJARAN DARI INDUSTRI TERPILIH - Sambodo, Maxensius Tri (Journal of Indonesian Economy and Business, 2008)
This paper aims to analyze the condition of Indonesian comparative advantage, based on internal and external factors analysis. Based on selected industries namely synthetic fiber, pulp and paper, travel goods and photographic and field research from five provinces, there are some lessons need to be done by government. There are threemajor findings from this study. First, there is no improvement in competitiveness without increasing value added and productivity. Second, high local content will help the industries to gain competitiveness. Third, currently, contribution of total factorproductivity and labor productivity are quite low for enhancing competitiveness. The study suggests government needs to develop up stream industries for supporting down stream industries. Further, promoting good and clean governance need to be part ofmicroeconomic reform.Keywords :Comparative advantage, value added, productivity, good and clean governance